Solving the apparent inconsistency between GSI and RIKEN estimates of 11Be dB(El)/dE. (December 2020) - Moschini, L; Capel, P
Abstract: 11 Be is the archetypical one-neutron halo nucleus. Due to its short lifetime, one of the only way to infer information about its exotic structure is to study reactions involving that nucleus, like breakup. When performed on a heavy target, like lead, breakup is dominated by the E1 transition from the bound state to the continuum, which is characterized by the dB ( E 1)/ dE . This strength has been inferred from two experiments, one performed at 520A MeV at GSI and the other at 69A MeV at RIKEN. Strangely the analyses of both experiments provide different E1 strengths. In this work, we reanalyze them using the eikonal approximation to study this discrepancy. In particular, we properly take into account relativistic effects, and include a consistent treatment of both nuclear and Coulomb interactions and their interference at all orders. The description of the 11 Be structure is provided by halo effective field theory (Halo-EFT). Our cross sections for the 11 Be breakup are in good agreement with both RIKEN and GSI data. The dB (E1)/ dE extracted from our 11 Be model is in agreement with the RIKEN result and ab initio predictions. We can conclude that the discrepancy between GSI and RIKEN dB (E1)/ dE arises from the method applied to extract this quantity. From our detailed analysis of the reaction, it seems that the most efficient way to extract the dB (E1)/ dE from the breakup cross section is to select the data at small angles, where the reaction is dominated by the Coulomb interaction.